Relationships Among Electrical Conductivity of Seed Leakage, Germination, Field Emergence Percentage and Some Seed Traits in Faba Bean (Vicia faba L.) - PEKSEN, ERKUT (Asian Journal of Chemistry, 2010)
This study was carried out to investigate the relationships among electrical conductivity (EC) of seed leakage at both 24th and 48th h, germination speed (GS), germination power (GP), field emergence percentage (FE) and some seed traits such as water absorption rate (WAR) of seeds during imbibition and seed coat ratio (SCR) in 15 faba bean (Vicia faba L.) cultivar/population. The results of the present studies revealed that faba bean cultivar/population differed for all investigated traits (p < 0.01). EC of seed steep water at 24th h showed similar trend to EC values determined at 48th h. EC ranged from 7.9 to 12.1 μS cm-1 g-1 at 24th h and 10.1 to 18.1 μS cm-1 g-1 at 48th h. In all cultivar/populations, the amount of water absorbed by the seeds at the end of the 24 h exceeded their initial dry weights. EC readings, at both 24th and 48th, didn’t give strong and reliable relationships to predict GS, GP and FE. Positive relationships were found between SCR and EC (r = 0.390** and r = 0.452** for 24th and 48th h, respectively) and WAR (r = 0.336*).